Improving Reading Comprehension of The Tenth Grade Office Administration Students of SMK Negeri 1 Pinrang by Using Experience-Text-Relationship (ETR) Method - Fitriani; Nurhamdah; Ismail Latif (Institut Agama Islam Negeri Parepare, 2018)
The objective of the research is to find out the improvement of the student’s reading comprehension after the researcher applies Experience-Text-Relationship (ETR) Method at the tenth grade office administration students of SMK Negeri 1 Pinrang. The research design in this research was pre-experimental method with one group pre-test, treatment and post-test. The population in this research was the tenth grade students’ office administration students of SMK Negeri 1 Pinrang consist of 105 students. The sample of this research was Class X Ap2 consist of 35 students. The researcher used purposive sampling because the teacher of SMK Negeri 1 Pinrang recommended this class. The researcher applies 30 items of multiple choice test. The result of this research indicated the students’ mean score in pre-test is 34.54 and mean score in post-test is 87.08. It can be concluded that the rate percentage in post-test was higher than the rate percentage in pre-test in teaching reading. This showed that Experience-Text-Relationship (ETR) method can improved students’ reading comprehension. Based on the result finding, the t-test was greater than the value of t-table (5.12 ≥ 2.021). This showed that Experience-Text-relationship (ETR) Method can improve students’ reading comprehension.